Analysis of Marriage Dispensation Factors: (Case Study of Class 1A Jombang Religious Decision Results) - Dimyati, Yayat (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
A marriage dispensation is an exception to the rules or law that is given to an applicant to enter into a marriage. In this research the author examines the decision on requests for marriage dispensation in the Jombang religious court. The focus of the research problem formulation is: 1. What is the level of requests for marriage dispensation in the Jombang religious court. 2. What is the background for submitting the application for marriage dispensation? 3. What are the judge’s considerations in determining the application for marriage dispensation in the Jombang religious court? The type of research is descriptive analysis research. This descriptive characteristic is to get a good, clear picture, and can provide as thorough an analysis of the data as possible about the object under study. The results of this research show that the factors behind the request for marriage dispensation are internal and external factors. The judge’s legal consideration in granting marriage dispensation is that there is Article 7 paragraph 2 of Law No. 1 of 1974 concerning deviations from the age limit for marriage. Court or other official appointed by both parents of the man and woman.